Maximum Plant Uptakes for Water, Nutrients, and Oxygen Are Not Always Met by Irrigation Rate and Distribution in Water-based Cultivation Systems - Blok, Chris; Jackson, Brian E.; Guo, Xianfeng; de Visser, Pieter H. B.; Marcelis, Leo F. M. (Frontiers in Plant Science, 2017)
Growing on rooting media other than soils in situ –i.e. substrate-based growing- allows for higher yields than soil-based growing as transport rates of water, nutrients and oxygen in substrate surpass those in soil. Possibly water-based growing allows for even higher yields as transport rates of water and nutrients in water surpass those in substrate, even though the transport of oxygen may be more complex. Transport rates can only limit growth when they are below a rate corresponding to maximum plant uptake. Our first objective was to compare Chrysanthemum growth performance for three water-based growing systems with different irrigation. We compared; multi-point irrigation into a pond (DeepFlow); one-point irrigation resulting in a thin film of running water (NutrientFlow) and multi-point irrigation as droplets through air (Aeroponic). Second objective was to compare press pots as propagation medium with nutrient solution as propagation medium. The comparison included DeepFlow water-rooted cuttings with either the stem 1 cm into the nutrient solution or with the stem 1 cm above the nutrient solution. Measurements included fresh weight, dry weight, length, water supply, nutrient supply and oxygen levels. To account for differences in radiation sum received, crop performance was evaluated with Radiation Use Efficiency (RUE) expressed as dry weight over sum of Photosynthetically Active Radiation. The reference, DeepFlow with substrate-based propagation, showed the highest RUE, even while the oxygen supply provided by irrigation was potentially growth limiting. DeepFlow with water-based propagation showed 15-17% lower RUEs than the reference. NutrientFlow showed 8% lower RUE than the reference, in combination with potentially limiting irrigation supply of nutrients and oxygen. Aeroponic showed RUE levels similar to the reference and Aeroponic had non-limiting irrigation supply of water, nutrients and oxygen. Water-based propagation affected the subsequent cultivation in the DeepFlow negatively compared to substrate-based propagation. Water-based propagation resulted in frequent transient discolorations after transplanting in all cultivation systems, indicating a factor, other than irrigation supply of water, nutrients and oxygen, influencing plant uptake. Plant uptake rates for water, nutrients and oxygen are offered as a more fundamental way to compare and improve growing systems.